Serum vitamin D level in healthy individuals versus patients with symptomatic and asymptomatic oral lichen planus: Vitamin D level in OLP - Lama H., Marssafy; Hussein, Fatma; Sadek, Hesham; Abdelghany, Wahdan (Cellular and Molecular Biology, 2022)
The aetiology of oral lichen planus (OLP) is multifactorial, having variable triggers. A role for vitamin D related to the immune system has been established. Vitamin D modulating effect is on the adaptive and innate immune responses. Our study aimed to compare serum levels of vitamin D in patients having different clinical symptoms of OLP (symptomatic or asymptomatic) with healthy individuals. Also, in this study, for further evaluation, the expression level of interleukin-17A and interleukin-6 (IL-17A and IL-6) was evaluated because the presence of active vitamin D reduces the expression of these pro-inflammatory factors. This study was included three groups with 30 volunteers in each. The first group included asymptomatic oral lichen planus patients (reticular or plaque-like lesions). The second group consisted of symptomatic oral lichen planus patients (atrophic or bullous-erosive lesions). In contrast, the third group consisted of healthy control subjects. The serum 25-hydroxyvitamin D was measured between the three groups and then correlated with clinical manifestation of oral lichen planus, either symptomatic or non-symptomatic. The Real-Time PCR technique was used to evaluate the expression of IL-17A and IL-6. Patients with symptomatic OLP (second group) had statistically significantly lower Vitamin D levels than asymptomatic OLP patients (first group). Healthy Controls (third group) exhibited statistically significantly higher vitamin D levels than OLP groups. The results of IL-17A and IL-6 genes expression showed that the presence of vitamin D had a statistically significant effect on reducing the expression of these two pro-inflammatory cytokines among symptomatic and asymptomatic OLP patients. Also, the results showed that there was a statistically significant difference between OLP patients (group I and II) and the control group (group III). In general, the current study results showed that lack of vitamin D had an important role in initiating or increasing the OLP’s severity.